Evaluasi Rasio Coal Blending terhadap Efisiensi Boiler Unit 7 Suralaya - Eri Prabowo; Trassanda Scudetto Widestomo Putra; Tegar Aris Prayoga (JTM : JURNAL TEKNIK MESIN, 2026)
This study evaluates the effect of coal blending ratio on boiler efficiency at Unit 7 of PT Indonesia Power Suralaya PGU. The analysis used low-rank coal (LRC) and medium-rank coal (MRC) with three blending ratios, namely 25L:75M, 50L:50M, and 75L:25M. Boiler performance was calculated using the indirect heat-loss method and compared with the direct input-output method. The main evaluated variables were coal quality, calorific value, moisture, ash, ultimate analysis, dry flue-gas loss, hydrogen-moisture loss, fuel-moisture loss, air-moisture loss, and specific fuel consumption. The results show that increasing the MRC fraction improves calorific value and tends to reduce moisture-related losses. The 25L:75M ratio consistently produced the best mixed-coal performance. In February 2020, the BB-2 mixture with 25L:75M achieved the highest indirect boiler efficiency of 85.798%, while the direct-method efficiency reached 73.845%. Therefore, the 25L:75M blending ratio is recommended as the most suitable operating option among the evaluated mixtures